REDUÇÃO DE VÍNCULOS NA SUBCONTRATAÇÃO: O CASO DE UMA EMPRESA DE INSTALAÇÕES PREDIAIS - Vicente, Matheus Simon; Haito, Ricardo Oviedo; Cardoso, Francisco Ferreira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Improving the quality of services performed by construction firms requires the understanding of the factors affecting their work. In several countries, most of the construction operations are performed by labor-intense trade and specialist contractors (EES), usually small and micro enterprises. Despite of many EES are qualified to perform the work they were hired; their results are unsatisfactory, because some factors do not depend of them, but their links with other agents. The objective of this paper is to discuss some options to reduce links in subcontracting practice. For this, a case study with an EES of plumbing was analysed using grounded description. As a result, factors related to reduction of links, via pre-assembly, were identified. Therefore, this work could help other EES to find ways to improve, among others, the reliability of their planning.